PERSEPSI REMAJA TERHADAP PERILAKU SEKSUAL PRANIKAH - Nurziani " "; Misrawati " "; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Premarital sex behavior occured almost in every city in Indonesia, included in Dumai, especially in Bukit Kapur district which is ever as the worst condition with the commercial sex workers. The purpose of this research is to explore the teenagers perception to premarital sex behavior. This research used qualitative method with descriptive phenomenology approach. This research was conducted to the female students of Senior High School 3 Dumai. There are six participants involved in this research by using purposive sampling techniques according to the inclusion criteria. This research used interview guidance. The analysis used was thematic analysis. The result of this research found four themes, namely: the perception of the teenagers to premarital sex behavior, the impact of the premarital sex behavior, the way to avoid premarital sex behavior and the teenagers’ expectation to the health workers. From this research, the participants have positive perception and do not support premarital sex behavior and understand about the threat and danger of premarital sex behavior eventhough they do not understand well about the impact of premarital sex behavior. The way of the teenagers to avoid premarital sex behavior is by involving or joining their school organization and in their neighborhood and expect to the health workers in order to keep giving health education about teens reproduction and the impact of premarital sex behavior.                                                                                                                                 Keywords: Premarital, perception, teenager, sex behavior.